(untitled) (Teacher’s World: Journal of Education and Research, 2023)
Disability has yet to be demystified in many aspects. It is ridden with social sigma and lack of understanding. Nevertheless, perspectives surrounding disability can change greatly, and this would help ensure equitable human rights for all. Other changes wrought by recent technological transformation have not only made our life easier but also broadened the inequality and opportunity gap to some context. Considering such matters affecting access and equity in education, and with the qualitative methodology at the core so as to capture and analyse detailed data in depth and with sufficient trustworthiness, this paper aims explored the consequences of digital technology utilization of students with disability in Higher Education (HE) in Bangladesh. The findings depicted how technology uses helped students with disability to empower themselves and to become mostly self-dependent. Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.102-111